Scarperation : an empirical inquiry into the role of scarcity in fostering cooperation between international river riparians - Kurukulasuriya, Pradeep (The World Bank, 2007)
The environment and security literature has argued that freshwater scarcity often leads to inter-state conflict, and possibly acute violence. The contention, however, ignores the long history of hydro-political cooperation exemplified by hundreds of documented agreements. Building on a theory that considers the relationship between scarcity and hydro-political cooperation, this paper empirically investigates why treaties are negotiated for some rivers and between some riparians, and not others. The paper suggests that long-term water scarcity has a significant influence on levels of cooperation. Additional variables considered include trade, level of governance among the riparian states, and the geography of the river. Findings confirm that cooperation and scarcity embody a concave (inverted U curve) relationship. Governance has a positive impact on cooperation. In addition, riparians may either arrange the use of their scarce water resources via a treaty or trade (and indirectly exchange [virtual] water). Scarcity, governance, and trade were found to be most salient in explaining levels of cooperation while geography is significant in some of the estimates